EFFECTIVENESS OF SUICIDE PREVENTION SKILLS TRAINING ON THE WILLINGNESS TO INTERVENE AND THE SELF-EFFICACY AMONG YOUNG ADULT STUDENTS - Mubarak Mansoor and Kiran Bashir Ahmad (Pakistan Journal of Clinical Psychology, 2022)
Objectives: Suicide has been a complex behavior which is considered to be one of a leading cause of preventable death among young adults if suicide ideation is identified at an early stage. Health organizations report that global suicide rates are declining except for young adults, therefore, this study aimed to measure effectiveness of suicide prevention skills training on the willingness to intervene against suicide and self-efficacy among young adult students. Design of the study: A Quantitative Pretest-Posttest quasi experimental research design was used. Place and Duration of the study: This study was conducted from Sep, 2020 till June, 2021 in different coaching centers of Karachi, Pakistan Sample and Method: Furthermore, purposive sampling technique was used to recruit young adult students (N=25) with an age range of 18-24 years with mean age of 20.72 (SD=1.54). The data was collected through The Willingness to Intervene against Suicide Questionnaire, and General Self-Efficacy Scale. Results and Conclusion: Results of study show significant moderate positive correlation between willingness to intervene against suicide and self-efficacy. Also, a significant improvement was found in the post intervention levels of willingness to intervene against suicide and self-efficacy among young adults with large effect size. This study has major implications for mental health and allied health care practitioners, and for policy makers in creating an informal safety net to prevent suicide by utilizing peer-to-peer support-based intervention.